Aspectos sócio-culturais e implicações ambientais das formas de uso e ocupação do espaço estuarino do Rio Timbó, estado de Pernambuco, Brasil - Cabral, Adilson Luiz (2001)
This paper had for purpose elaborate a diagnosis of the estuary area of the Timbó river – state of Pernambuco, concerning the use of the space and the occupation way, exploration and human interferences. Some sectors have been demarcated, 8 in the right margin (municipal district of Paulista), and 9 sectors in the left margin (municipal districts of Abreu e Lima and Igarassu). It had used semi structured questionnaires and done interviews with people that inhabit the neighborhood areas from the searching estuary (fishermen and dealers). Pondered matrixes of the environmental impacts (check-list) were built, as a model suggested by Tommasi (1994), modified for estuary areas; the matrix estuary’s space form of use, of the urban infrastructure conditions and the uses compatibility (as Diegues,1995), and the fishery forms in the estuary several sectors. With the application of these matrixes, it tried to decompose the analyzed environment in factors and indicators, emphasizing the structure of peripheral communities to the estuary and trying to evaluate the prejudices that man has been provoking to environment. It had verified that the searched area introduces a high level of degradation, with loss environmental quality clears evidences, especially in the right margin, where IQA’s values were smaller. Environmental quality critical levels (IQAs smaller than 50) were found in Maria Farinha and Nova Cruz. Among several cataloged impacts, garbage and sewages, landscape general alteration, invasion of public areas (including slums constructions), navigation and harbors and homemade fishing (including the utilization of explosives in some places) were the most highlighted. It had evidenced that commercial activities are in mostly nearest to the outlet and are directed essentially for recreation and tourism. The river inhabitants diagnosis social-environmental showed that most fishermen is illiterate and the fishing is made for men up to 89 years, that crop is essentially done by women up to 70 years, the number of children and pre-teenagers that participates in this activity is very large, fishing production is in retraction due the pollution and that seems it is causing a traditional link loss with fishing, evidenced by the small time of dwelling in the areas (less than 10 years, in general) and by the adoption of highly predatory practice, as the explosive and little net uses. Most fishing professionals owns their houses, with drinking water and electric power, being the estuary their main survival source. The imaginary of many people in this area is permeated by the belief in several kinds of ghosts, being a religious practice (Catholic in the right margin and evangelical in the left) very constant and present in all locations.